2019
DOI: 10.1038/s41746-019-0172-3
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning algorithm predicts diabetic retinopathy progression in individual patients

Abstract: The global burden of diabetic retinopathy (DR) continues to worsen and DR remains a leading cause of vision loss worldwide. Here, we describe an algorithm to predict DR progression by means of deep learning (DL), using as input color fundus photographs (CFPs) acquired at a single visit from a patient with DR. The proposed DL models were designed to predict future DR progression, defined as 2-step worsening on the Early Treatment Diabetic Retinopathy Diabetic Retinopathy Severity Scale, and were trained against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
133
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(144 citation statements)
references
References 32 publications
0
133
0
3
Order By: Relevance
“…Finally, a recent subject of application for CNN architectures is the analysis of ophthalmology images, e.g. for prediction of prognosis in diabetic retinopathy [19] or macular edema classification [20].…”
Section: Plos Onementioning
confidence: 99%
“…Finally, a recent subject of application for CNN architectures is the analysis of ophthalmology images, e.g. for prediction of prognosis in diabetic retinopathy [19] or macular edema classification [20].…”
Section: Plos Onementioning
confidence: 99%
“…Second, the SSS relies on two hand-crafted features and cannot receive other potentially risk-determining features. Recent work applying deep learning (DL) 14 has shown promise in the automated diagnosis and triage of conditions including cardiac, pediatric, dermatological, and retinal diseases 13,[15][16][17][18][19][20][21][22][23][24][25][26] , but not in predicting the risk of AMD progression on a large scale or at the patient level 27 . Specifically, Burlina et al reported on the use of DL for estimating the AREDS 9-step severity grades of individual eyes, based on CFP in the AREDS data set [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the potentially high number of radiomics features created on top of a rising number of clinical variables, powerful algorithms are needed to encompass and make all available data flourish. This is where ML algorithms thrive and have already shown tremendous results for a number of malignancies [42][43][44], but have, for now, barely been explored in ASCC. As an exception, using various ML algorithms including random forest and J48 decision trees, De Bari et al created a model predicting inguinal relapse with respective sensitivity, specificity and accuracy of 86.4%, 50% and 83.1% on the validation dataset (and superior results compared to logistic regression), highlighting the potential of such algorithms for ASCC care [45].…”
Section: Discussionmentioning
confidence: 99%